Pre-school education from a perspective of equality and equity. A reflection from the legal framework - Marchão, Amélia (2021)
This article reflects the trajectory of pre-school education in Portugal since the implementation of the Basic Law of the Educational System. The main objective is to discuss the Basic Law of the Educational System, in articulation with the Framework Law on Pre-School Education and the Curricular Guidelines for Pre-School Education, questioning the perspectives of equality and equity that are outlined there for children in Portugal. Altogether, this legal documentation considers the perspective of equality of opportunities in the access to pre-school education. However, the guarantee of the quality of the educational contexts and the children's learning, in the name of equity, is of greater uncertainty, although it is a concern of the legislation.Keywords: Pre-school education; legislation; equality; equity.